Respuesta :

Answer:

[tex]-\frac{5}{2}[/tex]

Step-by-step explanation:

Step 1: Put this into an equation

[tex]-\frac{5}{3} - x = \frac{5}{6}[/tex]

Step 2: Solve for x

[tex]-x = \frac{5}{6} + \frac{5}{3}[/tex]

[tex]-x = \frac{5}{2}[/tex]

[tex]x =- \frac{5}{2}[/tex]

Therefore you need to subtract [tex]-\frac{5}{2}[/tex] from [tex]-\frac{5}{3}[/tex] to get [tex]\frac{5}{6}[/tex]

Answer:i don’t know

Step-by-step explanation:I’m sorry dude I have no idea I tried doing it in the browser and I could not find an answer sorry